2021
DOI: 10.1016/j.jacbts.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signature of HFpEF

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A systems biology approach involving metabolomics and transcriptomics was used to assess HFpEF progression in the domestic cat subjected to aortic banding. 65 In this nonobese HFpEF model, cardiac hypertrophy and fibrosis occur at 1 month before diastolic dysfunction, and a few genes related to metabolism, including some associated with the mitochondrial ETC, were found to be altered at that time. Cardiac mitochondrial function was impaired, which along with the metabolic changes indicated impaired oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A systems biology approach involving metabolomics and transcriptomics was used to assess HFpEF progression in the domestic cat subjected to aortic banding. 65 In this nonobese HFpEF model, cardiac hypertrophy and fibrosis occur at 1 month before diastolic dysfunction, and a few genes related to metabolism, including some associated with the mitochondrial ETC, were found to be altered at that time. Cardiac mitochondrial function was impaired, which along with the metabolic changes indicated impaired oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 78%
“…These studies highlight the growing awareness that mitochondrial dysfunction is a common feature of HFpEF, particularly where diabetes and obesity are involved. 43,65,72 Whether mitochondrial dysfunction is causative or a consequence is yet to be established. Although no studies today have reported on MAMs in HFpEF, a better understanding of the processes by which mitochondria and ER/SR communicate is needed.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Early large animal models of HFpEF were based on single-hit perturbations, such as pressure overload in sheep ( Charles et al, 1996 ) or canine model of mild coronary microembolizations ( He et al, 2004 ), and exhibit only a portion of HFpEF features. Recently, slow-progressive pressure overload by aortic-constriction was used to establish a feline HFpEF model ( Wallner et al, 2017 ; Wallner et al, 2020 ; Gibb et al, 2021 ). Comprehensive phenotyping of this model showed many features of HFpEF, such as concentric LV hypertrophy and significant diastolic dysfunction ( Wallner et al, 2017 ; Wallner et al, 2020 ).…”
Section: Large Animal Models Of Hfpefmentioning
confidence: 99%